Construction of benzothiadiazole-based D-A covalent organic frameworks for photocatalytic reduction of Cr (VI) and synergistic elimination of organic pollutants. (2nd December 2022) - Qin, Na; Mao, Aojie; Li, Linqiang; Yang, Xiubei; Liu, Jing; Chen, Kongyao; Zhai, Lipeng; Liang, Ruowen; Mi, Liwei
Abstract: Covalent organic frameworks (COFs) are porous crystalline materials that have attracted considerable attention owing to their environmental-friendly photocatalytic characteristics. However, insufficient charge transfer and rapid charge recombination occur in the sunlight-driven photocatalytic performance of most COFs, which greatly impedes their photocatalytic activity. In this study, a donor-acceptor (D-A) COF, DTB-BT-COF, was synthesized using electron-deficient 4, 4'-(benzo[c] [1, 2, 5]thiadiazole-4, 7-diyl)dianiline (BT) and electron-rich 1, 3-dihydroxy-2, 4, 6-trialdehyde benzene (DTB). With its D-A structure, DTB-BT-COF exhibited outstanding photocatalytic performance for Cr(VI) reduction, which can be attributed to the integrative effect of the remarkable light absorption ability and more efficient separation of the photogenerated charge carriers. More significantly, DTB-BT-COF has proven to be a highly efficient photocatalyst in the removal of different aqueous contaminants with rhodamine B, methylene blue, or metronidazole as scavengers, which could be attributed to the synergetic effect between photocatalytic oxidation and reduction by individually consuming photogenerated holes and electrons. This study provided a new way to construct highly efficient D-A COFs for the purification of wastewaters containing mixed heavy metal ions and organic pollutants. Graphical abstract: Image 1 Highlights: A donor-acceptor (D-A) COF, DTB-BT-COF, was synthesized for the first time. The benzothiazole-containing D-A structure boosted the carrier separation efficiency. DTB-BT-COF exhibited outstanding photocatalytic performance for Cr(VI) reduction. DTB-BT-COF was a difunctional photocatalyst for removing of Cr(VI) and organics.